The role of PT. Raharja Services in Road Traffic Accidents (Study of Constitutional Court Decision Number 88/PUU-XV/2017 Regarding Review of Law Number 34 of 1964 concerning Compulsory Road Traffic Accident Insurance Funds) - Julianti, Firginia; Ginting, Budiman; Nasution, Faisal Akbar; Harris, Abdul (Formosa Journal of Applied Sciences, 2023)
The approach used in this research is normative juridical. using secondary data consisting of primary, secondary and tertiary legal materials, which are then analyzed using analytical descriptive analysis. The results of this research, PT. Jasa Raharja has carried out its responsibilities in accordance with the regulations that regulate it, but based on the rejection of the application as a whole by the judge in the Constitutional Court Decision No. 88/PUU-XV/2017 concerning Review of Law Number 34 of 1964 concerning Compulsory Road Traffic Accident Insurance Funds, it still has not been implemented. there is a regulation in the form of a law (rechtvacuum) regarding compensation for victims who experience a single accident, payment of compensation for victims who experience a single accident is only through Ex-Gratia which is the limited authority of PT. Jasa Raharja so that the presence of the state in providing social protection for single accident victims is very necessary.